(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2016)
The paper discusses the haunting narratives of amateur home movies in Péter Forgács’s multipart project Private Hungary (1988-2002), reading found-footage documentaries as a spectral repetition of a past era. It suggests that the tool-character of ‘revenant’ narratives may provide a new interpretative dimension forthe archival collection of Central European micro-narratives, presenting photographs, freeze-frames and colour filters as an innovative form of reiteration. The project’s found footage films employ re-personalize film form, re-writing forgotten archival stories over a backdrop of the grand récits (and national upheavals) of the Holocaust and ‘goulash’ communism. In particular, I read two Jewish stories, Dusi & Jenő (1989) and Free Fall (1996), in terms of their intermingling historical narratives, which ‘doubly occupied’ time, and formed the plurality ofrevenant visions. This ‘aesthetics of ruins’, which is presented as an effect of the coalescence of time, attempts to pose new questions and redefine our understanding of the visual heritage of past generations.